A construção da língua portuguesa escrita pelo surdo não oralizado - Silva, José Edmilson Felipe da (2009)
This work consists of a dialogue, between the assumptions "ferreriano" and "teberoskiano", on the development written, and its formation in the absence of speaking and hearing. How will be given the writing phonographic formation by a Deaf person? Ferreiro and Teberosky defend a moment, in the process of writing, so the child establishes the phonographic relation. Being the Deaf a non speaker person, incapable to discriminate the phonemes, as transposing this barrier and doing this writing? The expected moment for this transition, and the alternative found for Deaf citizens, constitute the essence of this research. We gather samples of writing of 20 (twenty) non speaker Deaf children. enrolled in two public schools in the city of Recife the capital of Pernambuco. Analyzing these writings (its content), we noticed that they presented particularities, compared with the chosen theoretical reference. Our initial hypothesis of a direct transition, from a concept of writing "pre-syllabic", to a concept of pseudo-alphabetic writing, proved to be correct. The absence of the concept of writing syllabic, syllabic-alphabetic and alphabetic is a basic feature, on the formation of writing by non speaker Deaf. Based on the theoretical framework of Ferreiro & Teberosky (1991), with its main and secondary hypotheses and referrals proposed by Bardin (1989, we classify and analyze each one of these writing, trying to understand all its features. The non phonetic of writing, shouldn t be understood not only as the processing of phonemes into graphemes, but also in the opposite direction, not the processing of graphemes into phonemes. We reclassify these atypical formations and rename them, therefore, the nomenclature used so far proved to be inappropriate, and leveling the writings, erasing their differences